On interest rate policy and asset bubbles - Franklin Allen; Gadi Barlevy; Douglas Gale (Federal Reserve Bank of Chicago, 2017)
In a provocative paper, Galí (2014) showed that a policymaker who raises interest rates to rein in a potential bubble will only make a bubble bigger if one exists. This poses a challenge to advocates of lean-against-the-wind policies that call for raising interest rates to mitigate potential bubbles. In this paper, we argue there are situations in which the lean-against-the wind view is justified. First, we argue Galí's framework abstracts from the possibility that a policymaker who raises rates will crowd out resources that would have otherwise been spent on the bubble. Once we modify Galí's model to allow for this possibility, policymakers can intervene in ways that raise interest rates and dampen bubbles. However, there is no reason policymakers should intervene to dampen the bubble in this case, since the bubble that arises in Galí's setup is not one that society would be better off without. We then further modify Galí's model to generate the type of credit-driven bubbles that alarm policymakers, and argue there may be justification for intervention in that case.
Keywords: 330